2011
DOI: 10.1097/rct.0b013e3181f5a610
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Tagging for CT Colonography

Abstract: Oral administration of a small volume hyperosmolar oral contrast agent 2 hours before CTC results in satisfactory colonic opacification in the majority of patients. Adding same-day fluid tagging in incomplete colonoscopy patients presenting for completion CTC should result in adequate fluid opacification for most of the colon, especially proximal segments not visualized at the time of incomplete colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Visual analysis confirmed that in 11% of same-day patients, no contrast had progressed into the colon, and only 56% of patients had contrast extending to the rectum. These findings are concordant with findings by other authors using a similar regimen (17), who nonetheless concluded that adequate colonic opacification was achieved. However, that study lacked comparison to a cohort who underwent standard CTC bowel preparation on a separate day, as in our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Visual analysis confirmed that in 11% of same-day patients, no contrast had progressed into the colon, and only 56% of patients had contrast extending to the rectum. These findings are concordant with findings by other authors using a similar regimen (17), who nonetheless concluded that adequate colonic opacification was achieved. However, that study lacked comparison to a cohort who underwent standard CTC bowel preparation on a separate day, as in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The first and most common is same-day CTC utilizing the prior OC prep, often supplemented with oral contrast after recovery from OC (17). This is often the more convenient option for the patient as they do not have to undergo further cathartic bowel preparation (assuming bowel prep for OC was adequate) and return on a separate day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tagging can be performed with an iodinated contrast agent following incomplete colonoscopy using a shortened interval protocol. In a study of 144 patients who ingested 20-30mL of iodinated contrast 2 hours prior to CT colonography and following incomplete colonosocopy, results showed that over 70% of patients had adequate tagging with contrast reaching the distal colon21.…”
Section: Useful Technical Tips For Ctc Performancementioning
confidence: 99%
“…For same-day CTC following incomplete OC, administering a small oral dose (20–30 mL) of Gastrografin often results in excess luminal fluid but is this opacification is still preferable to the alternative of not tagging. 17 The issue of residual solid stool related to “minimal prep” or non-cathartic approaches is important, as it may limit interpretation to a primary 2D approach, which results in suboptimal detection relative to a combined 3D/2D detection strategy (Fig 2). 12,18 …”
Section: Missed Lesions At Ctc (False-negative Interpretation)mentioning
confidence: 99%